Ene–yne cross-metathesis with ruthenium carbene catalysts - Fischmeister, Cédric; Bruneau, Christian (Beilstein Journal of Organic Chemistry, 2011)
Conjugated 1,3-dienes are important building blocks in organic and polymer chemistry. Enyne metathesis is a powerful catalytic reaction to access such structural domains. Recent advances and developments in ene–yne cross-metathesis (EYCM) leading to various compounds of interest and their intermediates, that can directly be transformed in tandem procedures, are reviewed in this article. In addition, the use of bio-resourced olefinic substrates is presented.
Keywords: catalysis; cross-metathesis; enyne; fatty acid esters; ruthenium